Management Of Acute Cholecystitis: A Case Report - Anpuchelvi, S.; Sritharan, G.; Vanathy, K. (Global Academic Research Institute Colombo, Sri Lanka, 2024)
In patient presenting with classic sign and symptoms of cholecystitis, the diagnosis is made based on confirmatory imaging studies. Here we discuss the case of presenting with symptoms of cholecystitis. A 33-year-old female patient reported at OPD at Herbal Health Care Hospital, Kokuvil, Jaffna in June 2022. She is a diagnosed case of acute cholecystitis with severe pain on abdomen, distention of abdomen and vomiting. As per the patient she had gradually developed these symptoms in past 3 years. In an attempt to get rid of these problems she consulted many Allopathic doctors and took allopathic drugs. But owing to no improvement in the condition the patient was advised to undergo surgery. As she was not willing to undergo surgery, she consulted Siddha Ayurveda physician and taken Siddha Ayurveda treatment for the same. Herbal formulation are better alternative natural remedies and it is safe, simple effective, self-administrative source of treatment. It is concluded that the combination of the siddha medical herbal treatment is effective in the management of Pithapaikalnoi (Gall stone)
Keywords: Pithapaikalnoi; Cholecystitis; Allopathic; Herbal health care